Role of School-Based Energy Supply and Conditional Cash Transfer Projects in Improving Primary Education: Case of Losimingori Primary School Project in Monduli District in Tanzania - Jeon, Only (Papers in Education and Development, 2022)
Abstract This is a descriptive paper to report on the role of school-based energy supply and conditional cash transfer projects in improving primary education in primary schools. Educational components included in the analysis are learning motivation among pupils and their attendance rate. Literature review, real time data analysis, surveys, and interviews were employed as appropriate research methods for this study in which both pupils and teachers were the subjects. Findings show that the motivation for education through the supply of energy was found to improve attendance. Second, the number of runaway students decreased due to battery charging time. Third, the teaching-learning time was stabilized through the digital attendance management system. Fourth, self-study time increased due to solar battery lighting. In addition to improving attendance rates, stabilizing teaching-learning time, and improving self-study time at home, it is recommended that studies on the relationship between academic achievement and the system satisfaction of parents and children should continue. Keywords: attendance rate, conditional cash transfer, improvement of education